THE ANALYSIS OF STUDENTS’ ANXIETY IN LEARNING WRITING AT THE 10TH GRADE OF VOCATIONAL HIGH SCHOOL - Alfiansyah, Fahmi; Jaufillaili, Jaufillaili; Hendriwanto, Hendriwanto (University of Muhammadiyah Purwokerto, 2017)
The ability to develop and produce written text is major achievement that the students must over hand. In writing, students can communicate and share knowledge, it also can support comprehension learning, to explore their feelings and beliefs. In EFL students tend to have difficulties in showing their ideas through impromtu way. The students lack do their exercise, feel confuse, not confidence, difficult to understand and comprehend the English From those problem it shows the students got an anxiety. Anxiety in writing shows a great role in giving negative influence for writing progress and writing acquisitions of students. In this study, the writer carried out the most dominant type and the main causes of students’ anxiety in learning writing. The writer used qualitative research method and descriptive case study research design in conducting the process of research. By using questionnaires of SLWAI (Second Language Writing Anxiety Inventory) and CWAI (Causes of Writing Inventory), and it also using interview to get more in-depth information of causes anxiety in learning writing. The writer was carried out in X Administrasi Perkantoran 3 of one vocational high school in Cirebon (Thirty six students in total and took 20 students as the participants). The findings of this qualitative research study indicated a somatic anxiety as the dominant type. Fear of negative comments and evaluation, time pressure and insufficient writing practice as its main causes of students’ anxiety in learning writing.DOWNLOAD ABSTRACT